POLITIK PEMBANGUNAN HUKUM PERJANJIAN INTERNASIONAL TERKAIT STATUS DAN KEDUDUKAN PERJANJIAN INTERNASIONAL DI TINJAU DARI PRAKTIK INDONESIA - Siti Sumartini (Faculty of Law, University of Muhammadiyah Malang, 2016)
International agreements (treaties) is one of the mechanisms in international relations as well as one of the sources of international law. Lack of understanding of what the public understanding of international agreements often giving riseto confuse in ournational legal system. Thereby also on the status and position of international treaties in the practice of Indonesia has not provided clarity about what the system is about to be followed by Indonesia.